P–672 Higher pregnancy outcomes in patients undergoing embryo transfer-under hormonal replacement therapy where an individualised Progesterone supplementation was applied on the day of β-hCG. (6th August 2021) - Alvarez, M; Racca, A; García, S; Martínez, F; González-Foruria, I; Parriego, M; Coroleu, B
Abstract: Study question: Does progesterone-supplementation (PS) from the day of β-hCG assessment improve pregnancy rates in embryo transfer-under hormonal replacement therapy (ET-HRT) in patient with Progesterone (P)<10.6 ng/mL? Summary answer: Reduced P on the β-hCG day is associated with lower pregnancy-rates and higher miscarriage-rate. PS from the same day showed significant increase of reproductive outcomes. What is known already: Up until now, in ART, very little has been done to understand whether the P intake should be personalized during the luteal phase. Most recent studies on the topic showed that low P levels on the day of ET-HRT or on the day before are associated with decreased pregnancy rates; however, when low P values are supplemented from the day before embryo-transfer (ET), similar results to cases with adequate P are reported. Nevertheless, little is known about the association between low P level, on the day of β-hCG (P- β-hCG) and PS from this day in ET-HRT, and pregnancy outcomes. Study design, size, duration: This is a single centre, cohort, retrospective study conducted at a university-affiliated fertility centre between January 2018 and June 2020 where PS took place from the day of positive β-hCG determination when P < 10.6 ng/mL. In total 789 ET-HRT cycles were analysed of which 239 were performed in both fresh and frozen heterologous ET-HRT (het-ET), 336 in homologous ET-HRT (hom-FET) and 214 in euploid ET-HRT (eu-FET) after preimplantation genetic testing for aneuploidies IVF cycles (PGT-A). Participants/materials, setting, methods: Women undergoing ET-HRT with normal P (>10.6ng/mL) on the day before ET were screened for P on the day of β-hCG. All women received vaginal P 200 mg/8 hours for the second part of HRT. PS was performed by adding P to the HRT when P- β-hCG was considered low (<10.6 ng/mL). Primary outcome: ongoing-pregnancy-rate (OPR); secondary outcome: miscarriage-rate (MR). Both were evaluated by considering PS on the day of β-hCG as a categorical variable. Main results and the role of chance: Patients characteristics were comparable between groups (het-ET, hom-FET and eu-FET) although significantly lower body mass index was found when P- β-hCG>10.6 ng/mL compared to the subgroup with P- β-hCG<10.6 ng/mL and no PS (p = 0.012). Overall clinical pregnancy rate was 52.1% with no-significant differences between groups (48.5% in het-ET, 52.9% in hom-FET and 54.7% in eu-FET). P- β-hCG was considered as adequate in 75.7% (311/411) ET-HRT with positive β-hCG and low in 24.3% (100/411), with no differences between groups. In case of positive β-hCG and P- β-hCG >10.6 ng/mL, OPR was 83.6% and MR was 16.4%, with no-significant differences between groups. Among the 100 low P- β-hCG, 80 ET-HRT received PS. In this subgroup OPR was 96.2% and MR was 3.8%, with no-significant differences between groups. In 20 out of 100 ET with P- β-hCG <10.6 ng/mL, no PS was added for different reasons. This group showed the lowest OPR (30%) and the highest MR (70%), again with no between-group differences according to het-ET, hom-FET or eu-FET. Miscarriage rate was significantly higher (p < 0.001) when P- β-hCG was <10.6 ng/mL and no PS was added to HRT compared to P- β-hCG <10.6 ng/mL but with PS, and also compared to the P- β-hCG >10.6 ng/mL group. Limitations, reasons for caution: The main limitation of the study is due to its retrospective nature and the small sample of patients with P- β-hCG<10.6 ng/mL that was not supplemented. Furthermore, the cut-off of P- β-hCG was arbitrarily decided upon previous studies, and lastly different routes of administration were considered for the PS. Wider implications of the findings: The results of this study showed that individualization of Progesterone supplementation in ET-HRT may be a crucial turn point in order to increase the pregnancy rates and decrease the miscarriage rates. An adequate PS should be considered in case of low P- β-hCG levels for both het-ET, hom-FET and eu-FET. Trial registration number: Not applicable